Batik Klasik: Aspek, Fungsi, Fiosofis dan Estetika Batik dalam Pandangan Budaya Nusantara - ., Dharsono (Jurnal Budaya Nusantara, 2014)
Batik is a painting or drawing on mori cloth created by using a tool called "canting ". People painting or drawing or writing on mori cloth with canting is called by membatik. It produces various forms and motifs of Batik and has special properties possessed by batik itself. The emergence of printed batik although it’s not as soft as handiwork batik, is enough to maintain the contained value of traditional batik. The Subsequent developments, batik is no longer used to accelerate the process, but accelerate the depiction of patterns and coloring, so the result of fabric batik is really similar to batik . This batik cloth is called " printing batik " . The dynamics of the Batik develop- ment divert the attention of Batik consumers. People turn to Batik motif textiles while Indonesian bourgeoisie was clothed in handiwork batik for the purposes of official events and formal parties. This dynamics will bring batik ( handiwork Batik) exclusively to the throne . Batik becomes a source of exaltation later on, then it will be a role model (philosophy) and a source of inspiration for the manufacture and further development of batik. Batik in a view of the archipelago culture alongside of its beautifulness (aesthetics), It’s also a guidance (teaching) painted on motives / classic batik pattern. That’s why that batik is a masterpiece heritage of the nations in the world from Indonesia, and It is now recognized widely as intangible and tangible heritage.